2022
DOI: 10.3390/molecules27185955
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics, Cheminformatics, and Systems Pharmacology Strategies Unveil the Potential Bioactives to Combat COVID-19

Abstract: Coronavirus disease (COVID-19) is a viral disease caused by the SARS-CoV-2 virus and is becoming a global threat again because of the higher transmission rate and lack of proper therapeutics as well as the rapid mutations in the genetic pattern of SARS-CoV-2. Despite vaccinations, the prevalence and recurrence of this infection are still on the rise, which urges the identification of potential global therapeutics for a complete cure. Plant-based alternative medicine is becoming popular worldwide because of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, based on the previous literature, 26 , 27 we selected important cancer-related genes, cell-cycle regulatory genes, and cytokine genes and analyzed their interconnections using in silico network analyses: STRING, GeneMANIA, and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. 28 , 29 The network analyses indicated that most of the selected genes are highly interlinked and involved in regulating apoptosis, lymphocyte differentiation, cytokine-mediated signaling pathways, and stress responses. Moreover, the analyses also identified genes connected with RCAS1 ( Figures 5 A–5C).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, based on the previous literature, 26 , 27 we selected important cancer-related genes, cell-cycle regulatory genes, and cytokine genes and analyzed their interconnections using in silico network analyses: STRING, GeneMANIA, and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. 28 , 29 The network analyses indicated that most of the selected genes are highly interlinked and involved in regulating apoptosis, lymphocyte differentiation, cytokine-mediated signaling pathways, and stress responses. Moreover, the analyses also identified genes connected with RCAS1 ( Figures 5 A–5C).…”
Section: Resultsmentioning
confidence: 99%
“…From the supplementary tables 2 and 3, it was clear that genes IL6, MMP9, ICAM1, and DPP4 were found to be common to both the phytocompound targeted receptors and COVID-19-associated signatures. So, these receptors were chosen for docking analysis to analyze the binding affinity between the targets and their respective phytocompounds [ 35 ]. Molecular docking studies were crucial in identifying the interactions of target compounds with their receptors at the atomic level.…”
Section: Discussionmentioning
confidence: 99%
“…Since nature is an inexhaustible source of remedies and therapeutic scaffolds, new potential drugs to be used in the fight against COVID-19 were often searched for from natural sources, especially plants [12][13][14], using highly diverse approaches such as transcriptomics, cheminformatics, and systems pharmacology with a holistic view [15]. Natural inhibitors of SARS-CoV-2 nonstructural protein (nsp10) were screened from a database containing 310 naturally isolated metabolites through various in silico selection methods including molecular similarity assessment, molecular fingerprint, docking studies, toxicity, ADMET (absorption, distribution, metabolism, excretion, and toxicity), and density-functional theory [16].…”
Section: Nature Against β-Coronavirusesmentioning
confidence: 99%